(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The research object of the article is the creativity of the Kazakh and Russian writer M.B. Zemskov. On the basis of his works, the images of city inhabitants in context of their mutual attraction and repulsion are considered. Also, the origins, traditions, and representatives of the «urban fiction» in Russian literature of the twentieth century are clarified. Additionally, in the frames of the given direction the problems of the direction, the specific image of the city and its inhabitants’ images are summarized. It substantiates the idea that, according to M. Zemskov, the city is a socio-cultural formation, filled with various forms of human activity, and the images of all the inhabitants of the city are interrelated. The main heroes of his works are intellectuals, adapting to the realities of life in a consumer society. The functions of contrast technique are discussed in details. As a result, it is concluded that the «internal» space of the heroes is correlated and compared with the «external» space of the city and its aggressive power through the contrast technique, performing the plot forming role.